Pemidanaan terhadap Pelaku Tindak Pidana Korupsi Melalui Double Track System - Anak Agung Gede Budhi Warmana Putra; Simon Nahak; I Nyoman Gede Sugiartha (Jurnal Preferensi Hukum, 2020)
This study aims to seek for deterrent effects for perpetrator of criminal acts of corruption that imposed with Double Track System concept. Double Track System represents the punishment system through two tracks which are criminal sanction and treatment. This study use normative law method. The resource of legal materials which used is primary legal material which is the legal rules and regulations and secondary legal material which is theories of law. The issues explored in this research are legal arrangement for offenders of criminal acts of corruption and punishment system against the offenders. The results showed that about the criminal acts of corruption and sanctions imposed on the offenders are set forth in Act No. 31 of 1999 Jo. Act No. 20 of 2001 about Decrement of Criminal Acts of Corruption and Punishment System and Double Track System against the perpetrators of criminal acts of corruption. The offenders are imposed imprisonment sanctions.